2010
DOI: 10.1089/jmf.2009.0157
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Tissue Distribution of14C-Labeled Grape Polyphenols in the Periphery and the Central Nervous System Following Oral Administration

Abstract: Grape polyphenols confer potential health benefits, including prevention of neurodegenerative diseases. To determine the absorption and tissue distribution of the complex grape polyphenol mixture, 14 C-labeled polyphenols were biosynthesized by grape cell suspension cultures, during co-incubation with radioisotopically labeled sucrose, and fractionated into polyphenolic subfractions. The pharmacokinetics and distribution of grape polyphenols into blood, brain, and peripheral interstitial fluid were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 31 publications
4
50
0
Order By: Relevance
“…The main AMFJ anthocyanins are glycosides of cyanidin. Recent studies have shown that polyphenols from berries can cross the blood-brain barrier (1,14,19) and do accumulate in the brain following long-term consumption (24).…”
Section: Discussionmentioning
confidence: 99%
“…The main AMFJ anthocyanins are glycosides of cyanidin. Recent studies have shown that polyphenols from berries can cross the blood-brain barrier (1,14,19) and do accumulate in the brain following long-term consumption (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, these signals were lower than those in corresponding samples of blood. The amount of residual label in the brain did not exceeded 1.7 % of the dose, and the radioactivity was spread homogenously over all the brain structures (Janle et al 2010 ).…”
Section: Polyphenols Penetration To Brain Tissuementioning
confidence: 91%
“…Single oral administration of 14 C-labeled grape polyphenols preparation in rats resulted in the appearance of radioactivity in cerebral interstitial fl uid sampled with microdialysis probes from hippocampus and also in brain slices obtained at 24-h postdose (Janle et al 2010 ). Maximal signals for labeled catechin/epicatechin (monomers, oligomers) peonidins, cyanidins, and cyanidin glycosides occurred in cerebral fl uid sampled between 0.75 and 1.5 h after grape polyphenols ingestion.…”
Section: Polyphenols Penetration To Brain Tissuementioning
confidence: 99%
“…Grape seed extracts also contain resveratrol, and therefore provide neuroprotection (269,270). Pharmacokinetic studies have affirmed that grape seed polyphenols abundantly distribute in the brain (271). The neuroprotective actions of resveratrol are mediated by enhancement of glutathione free radical scavenger activity (272,273), and reduction in AβPP-Aβ levels (274) due to increased clearance via the proteasome (275) or autophagy and lysosomal degradation (276).…”
Section: 54mentioning
confidence: 99%